Penerapan Manajemen Sumber Daya Manusia Dalam Meningkatkan Kinerja Karyawan di BAZNAS Kota Palembang - Fahrurrozi, M.; Pohan, Hasril Atieq (CV. ITTC INDONESIA, 2025)
This study aims to analyze the implementation of human resource management (HRM) and its impact on improving employee performance at the National Zakat Agency (BAZNAS) in Palembang City. The main focus lies on HRM functions such as workforce planning, recruitment, training and development, performance appraisal, and compensation. The method used is a qualitative descriptive approach with data collection techniques through interviews, observation, and documentation. The results of the study indicate that the implementation of structured and continuous HRM has a positive impact on improving employee performance, especially in terms of productivity, responsibility, and work discipline. Regular training and a fair performance appraisal system are dominant factors in supporting work effectiveness. In conclusion, well-implemented human resource management can be an important strategy in improving the quality and performance of employees in philanthropic institutions such as BAZNAS. This study recommends the need for continuous evaluation of the HRM system to adapt to the needs and dynamics of the organization.